1995
DOI: 10.1002/1097-4679(199507)51:4<526::aid-jclp2270510409>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Differential validity of the MMPI-2 subtle and obvious scales with psychiatric inpatients: Scale 2

Abstract: The construct and concurrent validity of the MMPI-2 Scale 2 Subtle and Obvious scales were examined for a group of 67 psychiatric inpatients. Validity coefficients for the Obvious scale were uniformly greater than those for the Full and Subtle scales. Subtle scale validity coefficients were negative and attenuated the validity of the Full clinical scale. Use of Obvious items resulted in more accurate prediction of assessed suicide risk, while inclusion of the Subtle items did not add any useful information in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…In what is undoubtedly a tribute to the psychometric properties of the Minnesota Multiphasic Personality Inventory (MMPI; Dahlstrom, Welsh & Dahlstrom,1972;Hathaway & McKinley,1948) and its revision, the MMPI-2 (Butcher, Dahlstrom, Graham,Tellegen & Kaemmer,1989), investigators continue to devise strategies to identify some psychometrically valid approach to the assessment of suicidal behaviors using these instruments (Boone, 1994;Boone, 1995;Sepaher, Bongar, & Greene, 1999). One approach that seems to hold promise is the use of the content scales (Butcher, Graham, Williams, & Ben-Porath,1990;Harris & Lingoes,1968).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In what is undoubtedly a tribute to the psychometric properties of the Minnesota Multiphasic Personality Inventory (MMPI; Dahlstrom, Welsh & Dahlstrom,1972;Hathaway & McKinley,1948) and its revision, the MMPI-2 (Butcher, Dahlstrom, Graham,Tellegen & Kaemmer,1989), investigators continue to devise strategies to identify some psychometrically valid approach to the assessment of suicidal behaviors using these instruments (Boone, 1994;Boone, 1995;Sepaher, Bongar, & Greene, 1999). One approach that seems to hold promise is the use of the content scales (Butcher, Graham, Williams, & Ben-Porath,1990;Harris & Lingoes,1968).…”
contrasting
confidence: 99%
“…Minnesota Multiphasic Personality Inventory-2 (MMPI-2; Butcher et al, 1989) The MMPI-2 is a 567-item measure of psychopathology and personality. Each item is rated true or false.…”
Section: Methodsmentioning
confidence: 99%
“…This latter criterion ruled out the use of so called subtle items that attempt to identify addictions without specifically mentioning alcohol and drugs. Furthermore, subtle items were not considered for the screen because obvious scales tend to have greater criterion validity than subtle scales for criminal history data (Osberg & Harrigan, 1999), and previous research has found subtle items to have poor reliability and to contribute little to predictive validity (Boone, 1994;Burgess, Campbell, & Zylberberg, 1984;Burkhart, Gynther, & Fromuth, 1980).…”
Section: Item Selectionmentioning
confidence: 99%
“…This is true for conditions, such as depression (Burkhart, Gynther, & Fromuth, 1980), mania (Snyter & Graham, 1984), psychopathy (Gynther, Burkhart, & Hovanitz, 1979; Snyter & Graham, 1984), and substance use disorders (Feldstein & Miller, 2007). Obvious items are also useful for the prediction of concerns, such as suicide risk, whereas subtle items largely fail to contribute useful information (Boone, 1995).…”
Section: Introductionmentioning
confidence: 99%